Method for manufacturing IPN imbibition swelling-compression elastic membrane material by thermally induced phase separation method

The film material with IPN interpenetrating polymer network structure was manufactured through the thermoform phase separation method, which solved the problem that the existing battery termination tape could not effectively compensate for gaps and lack of compression elasticity after absorbing liquid, achieved rapid swelling and compression elasticity of the film material, and improved the cycle life and safety of the battery.

CN119899593APending Publication Date: 2025-04-29FEICHENG MUYU NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202412000557.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The termination tape of existing lithium-ion batteries and sodium-ion batteries cannot effectively compensate for the reserved gap between the battery pole group and the inner wall of the shell after liquid absorption, and lacks compression elasticity, which affects the cycle life and safety of the battery.

Method used

The film material with an IPN interpenetrating polymer network structure is manufactured by the thermo-phase separation method. The film material that can absorb and swell and has compressive elasticity through high-temperature microcrosslinking and synchronous bidirectional thermal stretching of the ethylene-vinyl acetate copolymer EVA and the polyvinyl acetate homopolymer PVAc is formed.

Benefits of technology

The rapid swelling and compression elasticity of the film material in the thickness direction after liquid absorption is achieved, which can effectively compensate the gap between the battery electrode group and the inner wall of the shell, maintain stable contact between the electrode group, and improve the cycle life and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899593A_ABST
    Figure CN119899593A_ABST
Patent Text Reader

Abstract

A method for manufacturing an IPN liquid absorption swelling-compression elastic membrane material through a thermally induced phase separation method comprises the following steps that S1, a uniform thermodynamic solution is prepared, EVA and PVAc serve as raw materials for forming an IPN interpenetrating polymer network structure, high-temperature slight chemical crosslinking treatment is conducted through trace peroxide, and a three-dimensional network elastomer framework is obtained; the rest of high-molecular polymers which are not subjected to chemical cross-linking reaction are dispersed and distributed in the three-dimensional network elastomer skeleton; s2, rapid solidification-thermally induced phase separation; s3, carrying out hot isostatic pressing hydrothermal crosslinking treatment; s4, performing synchronous two-way hot stretching after unwinding; s5, coating a pressure-sensitive adhesive on a single side; and S6, slitting and packaging to obtain a finished product of the IPN imbibition swelling-compression elastic membrane material. The obtained membrane material is soaked in a dimethyl carbonate solvent for 48 hours, the swelling rate T48h / T0 in the thickness direction is 3-5 times, the weight rate W48h / W0 is 3.5-6.5 times, the membrane material subjected to liquid absorption swelling is pressurized for 24 hours by applying 0.01 MPa pressure in the thickness direction, and the compression permanent deformation rate in the thickness direction is smaller than 10% after the pressure is removed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion batteries and / or sodium ion batteries, and in particular to a film material having an IPN interpenetrating polymer network structure and a manufacturing method thereof, wherein the film material has a function of maintaining close contact between an electrode group and an inner wall of a shell by absorbing liquid and swelling inside the battery, and has a compressive elastic function of adapting to the volume change of the electrode group during charging and discharging. Background Art

[0002] Lithium-ion batteries and / or sodium-ion batteries are widely used in consumer electronics, electric vehicles, energy storage, and various small power fields due to their high energy density and no memory effect. In order to ensure the consistency of the battery after assembly and improve the cycle life and safety of the battery, it is hoped that the inside of the electrode group composed of the positive electrode plate / diaphragm / negative electrode plate can always maintain close contact during charging / discharging during the design, manufacturing and subsequent use of the battery, so that the lithium ion transmission path remains relatively stable; for large square batteries and cylindrical batteries, for the convenience of assembly, the electrode group is generally designed to maintain a small reserved gap with the inner wall of the shell when entering the shell. Generally, for cylindrical batteries, the single-side reserved gap ranges from 50-80 microns. For large square aluminum shell batteries or blade batteries, the single-side reserved gap ranges from 50 -150 microns. When designing a battery, it is hoped that the termination tape wrapped around the outer ring of the electrode group will have the function of compensating for the reserved gap by swelling in volume after absorbing electrolyte, especially it is hoped that the swelling and deformation of the termination tape in the thickness direction after absorbing electrolyte can effectively compensate for the reserved gap, and maintain stable contact between the electrode group and the inner wall of the battery shell and the inside of the electrode group; in order to improve the cycle life of the battery, it is hoped that the termination tape will swell and deform in the thickness direction after absorbing electrolyte without dissolving, and the termination tape after swelling by liquid absorption is hoped to have compression elasticity function, which is conducive to the dimensional change in the thickness direction of the adaptive electrode group during charging and discharging. The termination tape with the above swelling function in the thickness direction after absorbing liquid and the dual functions of compression elasticity has positive value for improving the safety, consistency and cycle life of the battery.

[0003] Chinese invention patent application publication document CN115093803A proposes a thickness swelling tape for lithium-ion batteries and a preparation method thereof, which adopts a PET substrate layer, a swellable substrate layer, and a pressure-sensitive adhesive layer. The swellable substrate layer is formed by hot-melt coating on the surface of the PET substrate layer. The invention utilizes the high strength of the PET substrate layer and the limited bonding force between the PET substrate layer and the swellable substrate layer after corona treatment to prevent the swellable substrate layer from swelling in the MD / TD direction, and focuses on achieving the technical purpose of swelling in the thickness direction; the swellable substrate layer of the invention adopts polytrimethylene carbonate, polybutylene succinate, and isocyanate or p-toluenesulfonic acid curing agent, which are stirred evenly and then hot-melt coated; this method is prone to the presence of unreacted small molecular monomer residues, which is likely to affect the rate performance and cycle life of the battery.

[0004] There is also a tape substrate on the market that uses a biaxially oriented polystyrene film OPS as the expansion functional layer. A pressure-sensitive adhesive is coated on the surface of the OPS film. The OPS dense film is easily dissolved after contacting ester solvents in the electrolyte, such as typical dimethyl carbonate DMC or diethyl carbonate DEC. Although it has a certain viscosity after dissolution and has a certain function of compensating for the gap between the electrode group and the inner wall of the battery shell, and has a function of preventing the electrode group from moving axially, this type of expansion tape is unevenly distributed after absorbing liquid and dissolving, has poor compression elasticity, and seriously insufficient elastic recovery performance, so it does not contribute much to the cycle life and consistency of the battery.

[0005] In order to overcome the shortcomings and deficiencies of the prior art and products, the present invention is proposed. Summary of the invention

[0006] The present invention provides a method for manufacturing an IPN liquid absorption swelling-compression elastic film material by a thermally induced phase separation method, characterized in that the method for manufacturing an IPN liquid absorption swelling-compression elastic film material by a thermally induced phase separation method comprises the following process steps:

[0007] Step 1 Preparation of uniform thermodynamic solution

[0008] Ethylene-vinyl acetate copolymer EVA and polyvinyl acetate homopolymer PVAc, which have thermodynamic compatibility after melting at high temperature, are used as raw materials for constituting an IPN interpenetrating polymer network structure, and a trace amount of peroxide is used for high-temperature slight chemical cross-linking treatment. Through free radical addition reaction, a part of ethylene-vinyl acetate copolymer EVA and polyvinyl acetate homopolymer PVAc form a three-dimensional network-like elastomer skeleton after chemical cross-linking, and the remaining high-molecular polymers that do not undergo chemical cross-linking reaction are dispersed in the three-dimensional network-like elastomer skeleton in a physically entangled state; the added amount of peroxide in the above raw materials accounts for 0.15-0.30wt.%; EVA and PVAc raw materials are first mixed uniformly at a temperature range of 100-130°C to form a uniform thermodynamic solution / melt, and then a peroxide cross-linking agent is added, and the mixing is continued for 5-30min, and the melt is kept in a slightly chemically cross-linked thermoplastic state, and the melt is fed into a flat die head for extrusion molding into a sheet;

[0009] Step 2 Rapid solidification-thermally induced phase separation

[0010] The high-temperature melt sheet extruded from the flat die is rapidly solidified and cast on the surface of a mirror roller with water cooling inside. The rapidly solidified sheet forms an IPN interpenetrating polymer network structure after EVA and PVAc are separated at low temperature based on the principle of thermally induced phase separation. The cooled sheet is then composited and rolled together with an inert fluoroplastic film, wherein the fluoroplastic film includes one of a PFA film, a FEP film or a PTFE film.

[0011] Step 3 Hot isostatic pressing and hydrothermal crosslinking treatment

[0012] Place the wound composite coil and its steel mandrel in a horizontal position as a whole into the autoclave. After sealing the autoclave cover, first introduce cold water or hot water with a temperature below 80°C into the autoclave, then fill the autoclave with high-pressure gas, adjust the air pressure inside the autoclave to 0.80MPa-1.80MPa, start heating, and gradually heat to a temperature range of 130°C-170°C. Keep the materials in the autoclave in a hot isostatic pressing state of high temperature and high pressure for hydrothermal crosslinking treatment for 0.5-4 hours; then cool down to below 60°C while maintaining a high pressure of not less than 0.80MPa in the autoclave; finally reduce the pressure in the autoclave to normal pressure, and take the materials out of the autoclave;

[0013] Step 4 Synchronous bidirectional heat stretching after unwinding

[0014] After the material is taken out of the kettle, it is peeled and unwound, and the unwound sheet is subjected to synchronous bidirectional heat stretching. The sheet is subjected to synchronous bidirectional heat stretching at a temperature range of 85-115°C, with a longitudinal stretching ratio of 2-4 times and a transverse stretching ratio of 2-4 times. The film formed after the synchronous bidirectional heat stretching is cooled and then rolled up or rolled up after online coating of pressure-sensitive adhesive;

[0015] Step 5: Single-sided coating of pressure-sensitive adhesive

[0016] The film material formed after the simultaneous biaxial heat stretching is subjected to corona treatment on one side, and then a pressure-sensitive adhesive is coated on one side of the corona side;

[0017] Step 6 After cutting and packaging, the finished IPN liquid absorption swelling-compression elastic film material is obtained.

[0018] After the IPN liquid absorption swelling-compression elastic film obtained by the manufacturing method of the present invention is immersed in dimethyl carbonate DMC solvent at 23-28°C for 48 hours, the swelling ratio T in the thickness direction is 48h / T0 is between 3-5 times, where T 48h Refers to the thickness of the membrane after 48 hours of swelling, T0 is the initial thickness of the membrane before immersion; swelling weight ratio W 48 h / W0 is between 3.5-6.5 times, where W 48h It refers to the total weight of the membrane after absorbing liquid and swelling for 48 hours, W0 is the initial weight of the membrane before being immersed in the solvent; after the membrane has absorbed liquid and swelled, a pressure of 0.01MPa is applied in the thickness direction at an ambient temperature of 5-15°C, and the pressure is maintained for 24 hours. After the pressure is removed, the compression permanent deformation rate in the thickness direction is less than 10%.

[0019] The IPN liquid absorption swelling-compression elastic film obtained by the manufacturing method of the present invention can attract ester small molecule solvents such as dimethyl carbonate DMC in the organic electrolyte into the micro-crosslinked IPN polymer three-dimensional network under capillary action after contacting the organic electrolyte, thereby achieving swelling in the thickness direction; limited by the physical restriction effect of the IPN interpenetrating polymer network structure, the polyvinyl acetate homopolymer PVAc polymer dispersed in the three-dimensional network-like elastomer skeleton formed after chemical crosslinking will not dissolve in the DMC ester solvent due to entanglement, thereby achieving the technical purpose of swelling without dissolving. The micro-crosslinked IPN polymer stereo network of the present invention provides compression elasticity; the weight percentage of EVA in the raw material to the sum of (EVA+PVAc) is between 35-50%, the content of vinyl acetate VA in the EVA raw material is between 27-55wt%, and the melt index MI (190 / 2.16kg) of the EVA raw material is between 20-150g / 10min; PVAc in the raw material can be dissolved in dimethyl carbonate DMC and ethyl acetate when it exists independently, and its viscosity (10% ethyl acetate solution, 20°C) is between 7-35mPa*s;

[0020] The technical design of the present invention is further explained below.

[0021] The liquid-absorbing swelling-compression elastic film material of the IPN interpenetrating polymer network structure of the present invention adopts ethylene-vinyl acetate copolymer EVA and polyvinyl acetate homopolymer PVAc which are mutually compatible at high temperature to form the raw materials of the interpenetrating polymer network structure, because both of the molecular structures of the two polymer raw materials are saturated main chain structures and contain common vinyl acetate VA segments, and after melting at high temperature, the two polymer raw materials can be mixed into a uniform thermodynamic solution / melt to achieve molecular-level mixing uniformity, and after rapid solidification and cold casting crystallization, the interpenetrating network structure formed after phase separation is relatively uniform; after the present invention uses a trace amount of peroxide for high-temperature micro-crosslinking treatment, the ethylene-vinyl acetate copolymer The polymer EVA is mainly used to form a chemically cross-linked three-dimensional network elastomer skeleton. As the main chain of ethylene-vinyl acetate copolymer does not contain unsaturated double bonds, the chemically cross-linked EVA has good chemical stability and durability when used in batteries; after low-temperature phase separation and synchronous biaxial heat stretching, the polyvinyl acetate homopolymer PVAc polymer dispersed in the EVA three-dimensional network elastomer skeleton can attract ester small molecule solvents such as dimethyl carbonate DMC into the polymer network under capillary action based on the principle of like dissolves like. The IPN interpenetrating polymer network structure of liquid swelling-compression elastic film can achieve rapid swelling; however, due to the microstructural limitations of the interpenetrating polymer three-dimensional network, the dispersed The polyvinyl acetate homopolymer PVAc polymer distributed in the three-dimensional network-like elastomer skeleton with EVA as the main body will not dissolve in the DMC ester solvent due to physical entanglement, that is, it will not dissolve from the three-dimensional network-like elastomer skeleton. The PVAc polymer therein forms a gel with the ester solvent absorbed into the three-dimensional network of the polymer; the weight percentage of EVA in the raw material to the sum of (EVA+PVAc) is between 35-50%. Too low EVA content in the raw material will reduce the compression elasticity of the IPN liquid absorption swelling-compression elastic film product, and may also cause the PVAc in the film to dissolve, which is not conducive to the rate characteristics, cycle life and consistency of the battery; the raw material If the EVA content is too high, the swelling ratio of liquid absorption in the thickness direction will be reduced, which is not conducive to the function of compensating the gap; the content of vinyl acetate VA in the EVA raw material is between 27-55wt%, and the low VA content in the ethylene-vinyl acetate copolymer polymer segment means that the polyethylene content is too high, EVA is easy to crystallize, and the restriction function on swelling is too strong, and the swelling ratio of the swelling tape substrate will be reduced; the high VA content in the ethylene-vinyl acetate copolymer polymer segment is easy to affect the efficiency of peroxide high-temperature cross-linking, and it is not easy to form a chemically cross-linked body structure, which is not conducive to the film material maintaining the compressive elastic function after liquid absorption and swelling; the melt index MI (190 / 2.16kg) is between 20-150g / 10min. Too low a melt index means that the molecular weight is too large, which is not conducive to the uniformity of mixing processing. Too high a melt index means that the molecular weight is too low, which is not conducive to the mechanical strength of the swollen film material. PVAc in the raw material can be dissolved in dimethyl carbonate DMC and ethyl acetate when it exists alone, and its viscosity (10% ethyl acetate solution, 20°C) is between 7-35mPa*s. Too low a viscosity means that the molecular weight of PVAc is too low, and it is easy to be dissolved out of the EVA three-micro network by ester small molecule solvents, which will affect the viscosity and conductivity of the electrolyte and is not conducive to the rate performance of the battery. The present invention uses a small amount of peroxide crosslinking agent to provide active oxygen through thermal decomposition at high temperature, uses the active oxygen to attack the hydrogen of the main chain and side chain of the ethylene-vinyl acetate copolymer polymer, and uses the generated free radicals to achieve chemical crosslinking and addition reaction, thereby constructing an IPN interpenetrating polymer network structure that can quickly absorb electrolyte swelling and maintain compressive elasticity. In contrast, although ordinary physically crosslinked thermoplastic rubber materials also have the characteristics of liquid absorption and swelling, the physical entanglement network of the polymer presents an internal plasticization effect. When subjected to compression or shear stress after swelling, the physically crosslinked thermoplastic rubber is prone to plastic deformation, has poor compressive elasticity, and its mechanical properties after swelling are also greatly reduced. The present invention uses synchronous bidirectional heat stretching on the sheet in a thermoplastic state after chemical crosslinking. On the one hand, the technical purpose is to improve the mechanical strength of the film material in the MD and TD directions. The technical purpose of the other aspect is that the sheet in the heated state does not have the process problem of sticking to the roller during the synchronous bidirectional heat stretching. The technical purpose of the third aspect is that after the synchronous bidirectional heat stretching, the mesh structure of the IPN three-dimensional interpenetrating network structure is optimized, that is, from the extremely fine interpenetrating structure after the rapid solidification casting to the moderately opened mesh structure after the synchronous bidirectional heat stretching, which is beneficial for achieving rapid liquid absorption and easy to achieve thickness direction swelling; the IPN liquid absorption swelling-compression elastic film product has a good gap compensation function after liquid absorption swelling, and the positive electrode sheet / diaphragm / negative electrode sheet inside the electrode group can maintain close contact; after liquid absorption swelling, it also maintains excellent compression elasticity, which is beneficial to the dynamic compression function between the battery electrode groups, and can adapt to the volume expansion / contraction effect generated by the charging and discharging of the active materials in the electrode sheet, which is beneficial to the cycle life and consistency of the battery. .

[0022] Figures and their descriptions

[0023] Attached Figure 1The present invention is a schematic diagram of the equipment for the front process of manufacturing the IPN liquid absorption swelling-compression elastic film material, rapid solidification casting and composite winding, wherein 1 is an extruder, 2 is a flat die head, 3 is a fluororubber pressure roller, 4 is a mirror roller with a double spiral flow channel for water cooling inside, and the melt can achieve rapid solidification and phase separation; 5 is a fluororubber pressure roller, 6 and 7 are auxiliary cooling rollers, 8 is a roller, 9 is a thickness gauge, 10 is a sheet material that undergoes extrusion casting, rapid wind coagulation, and thermally induced phase separation and crystallization to become an IPN interpenetrating polymer network structure, 11 is a roller, 12 is a non-stick fluoroplastic film, 13 is a fluoroplastic film unwinding device, 14 is a composite winding device, and 15, 16, 17, and 18 are rollers.

[0024] Attached Figure 2 It is a schematic diagram of the hot isostatic pressing hydrothermal cross-linking treatment device of the composite coil of the present invention, wherein 1 is the autoclave cover, 2 is the autoclave body of the autoclave, 3 is the central support core shaft, 4 is the composite coil, 5 is the ground support of the autoclave, 6 is the jacket, 7 is water, 8 is the drain valve, 9 is the inlet of the jacket circulating heating medium, 10 is the inlet and outlet control valve of the high-pressure gas, 11 is the pressure gauge, 12 is the safety valve, 13 is the water inlet control valve, and 14 is the outlet of the jacket circulating heating medium.

[0025] Attached Figure 3 The present invention is a process flow chart of the manufacturing process of the IPN interpenetrating polymer network structure liquid absorption swelling-compression elastic film material.

[0026] In order to better understand the present invention, the following are some embodiments. Example

[0027] Embodiment 1:

[0028] The method for manufacturing IPN liquid absorption swelling-compression elastic film by thermally induced phase separation method includes the following process steps:

[0029] Step 1 Preparation of uniform thermodynamic solution

[0030] The raw material of ethylene-vinyl acetate copolymer EVA adopts the grade EVA-3345 produced by Arkema, whose VA content is 33%, and whose melt index is 45g / 10min. The weight percentage of EVA-3345 in the raw material to the sum of (EVA+PVAc) is 43%; the PVAc in the raw material adopts the grade S1115 polyvinyl acetate homopolymer produced by Yantai Norda Company, and its viscosity (10% ethyl acetate solution, 20°C) is between 9-11mPa*s; the manufacturing method of interpenetrating polymer network swelling tape substrate, the above EVA and PVAc raw materials are first mixed uniformly at 115-120°C according to the ratio of 44:56 parts by weight, and then a peroxide crosslinking agent BIPB---0.023 parts by weight is added, and the mixing is continued for 15min, the melt is kept in a slightly crosslinked thermoplastic state, the melt is fed into a flat die head, and extruded into a sheet, and the sheet thickness is about 450 microns;

[0031] Step 2 Rapid solidification-thermally induced phase separation

[0032] The high-temperature melt sheet extruded from the flat die is rapidly solidified and cast on the surface of a mirror roller with internal water cooling. The outer diameter of the mirror roller is 900 mm, the inlet temperature of the cooling water is between 20-25°C, and the inlet flow rate is between 25-30 cubic meters / hour; the cooled sheet is composited and rolled together with an inert non-adhesive fluoroplastic film, and the fluoroplastic film, i.e., the interlayer isolation film, is a FEP film;

[0033] Step 3 Hot isostatic pressing and hydrothermal crosslinking treatment

[0034] The rolled composite coil and its steel mandrel are placed horizontally in an autoclave. After the autoclave cover is sealed, hot water at about 50-60°C is introduced into the autoclave, and then compressed air is introduced into the autoclave. The air pressure inside the autoclave is adjusted to 1.20MPa, and heating is started. The temperature is gradually heated to 150-155°C. The materials in the autoclave are kept in a hot isostatic pressing state at high temperature and high pressure for hydrothermal crosslinking treatment for 2 hours. Then, the temperature is lowered to below 50°C while maintaining a high pressure of not less than 1.20MPa in the autoclave. Finally, the pressure in the autoclave is reduced to normal pressure, and the materials are discharged from the autoclave.

[0035] Step 4 Synchronous bidirectional heat stretching after unwinding

[0036] After the material comes out of the kettle, it is peeled and unwound, and the unwound sheet is subjected to synchronous bidirectional heat stretching. The sheet is subjected to synchronous bidirectional heat stretching at a temperature range of 95-105°C, with a longitudinal stretching ratio of 3 times and a transverse stretching ratio of 3 times. The thickness of the film formed after synchronous bidirectional heat stretching is about 45 microns, and it is rolled up after cooling;

[0037] Step 5: Single-sided coating of pressure-sensitive adhesive

[0038] The film material formed after the synchronous biaxial heat stretching is subjected to corona treatment on one side, and then a pressure-sensitive adhesive is coated on one side of the corona side;

[0039] Step 6 After cutting and packaging, the finished IPN liquid absorption swelling-compression elastic film material is obtained.

[0040] After the IPN liquid absorption swelling-compression elastic film obtained by the manufacturing method of the present invention is immersed in dimethyl carbonate DMC solvent at 23-25°C for 48 hours, the swelling ratio T in the thickness direction is 48h / T0 is 3.7 times, and the swelling weight ratio W 48h / W0 is 5.9 times; after the membrane material absorbs liquid and swells, a pressure of 0.01MPa is applied in the thickness direction at an ambient temperature of 10-15°C, and the pressure is maintained for 24 hours. After the pressure is removed, the compression permanent deformation rate in the thickness direction is less than 7%.

Claims

1. A method for manufacturing an IPN liquid absorption swelling-compression elastic membrane material by a thermally induced phase separation method, characterized in that: The method comprises the following steps: Step 1 Preparation of uniform thermodynamic solution Ethylene-vinyl acetate copolymer EVA and polyvinyl acetate homopolymer PVAc, which have thermodynamic compatibility after melting at high temperature, are used as raw materials for constituting an IPN interpenetrating polymer network structure, and a trace amount of peroxide is used for high-temperature slight chemical cross-linking treatment. Through free radical addition reaction, a part of ethylene-vinyl acetate copolymer EVA and polyvinyl acetate homopolymer PVAc form a three-dimensional network-like elastomer skeleton after chemical cross-linking, and the remaining high-molecular polymers that do not undergo chemical cross-linking reaction are dispersed in the three-dimensional network-like elastomer skeleton in a physically entangled state; the added amount of peroxide in the above raw materials accounts for 0.15-0.30wt.%; EVA and PVAc raw materials are first mixed uniformly at a temperature range of 100-130°C to form a uniform thermodynamic solution / melt, and then a peroxide cross-linking agent is added, and the mixing is continued for 5-30min, and the melt is kept in a slightly chemically cross-linked thermoplastic state, and the melt is fed into a flat die head for extrusion molding into a sheet; Step 2 Rapid solidification-thermally induced phase separation The high-temperature melt sheet extruded from the flat die is rapidly solidified and cast on the surface of a mirror roller with water cooling inside. The rapidly solidified sheet forms an IPN interpenetrating polymer network structure after EVA and PVAc are separated at low temperature based on the principle of thermally induced phase separation. The cooled sheet is then composited and rolled together with an inert fluoroplastic film, wherein the fluoroplastic film includes one of a PFA film, a FEP film or a PTFE film. Step 3 Hot isostatic pressing and hydrothermal crosslinking treatment Place the wound composite coil and its steel mandrel in a horizontal position as a whole into the autoclave. After sealing the autoclave cover, first introduce cold water or hot water with a temperature below 80°C into the autoclave, then fill the autoclave with high-pressure gas, adjust the air pressure inside the autoclave to 0.80MPa-1.80MPa, start heating, and gradually heat to a temperature range of 130°C-170°C. Keep the materials in the autoclave in a hot isostatic pressing state of high temperature and high pressure for hydrothermal crosslinking treatment for 0.5-4 hours; then cool down to below 60°C while maintaining a high pressure of not less than 0.80MPa in the autoclave; finally reduce the pressure in the autoclave to normal pressure, and take the materials out of the autoclave; Step 4 Synchronous bidirectional heat stretching after unwinding After the material is taken out of the kettle, it is peeled and unwound, and the unwound sheet is subjected to synchronous bidirectional heat stretching. The sheet is subjected to synchronous bidirectional heat stretching at a temperature range of 85-115°C, with a longitudinal stretching ratio of 2-4 times and a transverse stretching ratio of 2-4 times. The film formed after the synchronous bidirectional heat stretching is cooled and then rolled up or rolled up after online coating of pressure-sensitive adhesive; Step 5: Single-sided coating of pressure-sensitive adhesive The film material formed after the synchronous biaxial heat stretching is subjected to corona treatment on one side, and then a pressure-sensitive adhesive is coated on one side of the corona side; Step 6 After cutting and packaging, the finished IPN liquid absorption swelling-compression elastic film material is obtained.

2. The method according to claim 1, characterized in that After the obtained IPN liquid absorption swelling-compression elastic film was immersed in dimethyl carbonate DMC solvent at 23-28°C for 48 hours, the swelling ratio T in the thickness direction was 48h / T0 is between 3-5 times, swelling weight ratio W 48h / W0 is between 3.5-6.5 times. After the membrane material is swollen by liquid absorption, a pressure of 0.01MPa is applied in the thickness direction at an ambient temperature of 5-15°C. The pressure is maintained for 24 hours. After the pressure is removed, the compression permanent deformation rate in the thickness direction is less than 10%.

Citation Information

Patent Citations

  • Thickness swelling adhesive tape for lithium ion battery and preparation method of thickness swelling adhesive tape

    CN115093803A